ANALISIS STRATEGI PENGEMBANGAN BISNIS MENGGUNAKAN SMART BUSINESS MAP PADA D’WAN SHOES - Salwa Rizki Desi Ayunda Sari; Imanuddin Hasbi (DAS Institute, 2022)
In the last two years, the Covid-19 pandemic has hit many countries, including Indonesia. The impact of this is that many parties are harmed so many businesses change their way of selling, namely by utilizing the use of the internet. In contrast to this phenomenon, one of the entrepreneurs in the Cibaduyut Shoe Center area, namely D'Wan Shoes, still sells conventionally by implementing the Business to Business system. Therefore, the purpose of this research is to develop and map a new business strategy for D'Wan Shoes using a Smart Business Map. The method used in this research is descriptive qualitative analysis by analyzing the Playing Field and Market Landscape sections of D'Wan Shoes. Based on the results of the research that has been done, it can be seen that there are still shortcomings that need to be evaluated to be clearer and structured. The conclusion of this research is that D'Wan Shoes needs to do market research before launching the product, expand the target market to all over Indonesia, and make product innovations such as shoe models and sales methods, namely providing custom services. If things happen that are beyond D'Wan Shoes' control, such as government policies, changes in technology, and consumer behavior, D'Wan Shoes needs to prepare alternative ideas or adapt to these changes. Then they can take advantage of the production process to become the company's value proposition to compete with competitors. Planned campaigns and promotions will be carried out through social media by conducting paid promotions from features that already exist in several applications (Facebook Ads, Instagam Ads, Tiktok Ads), then using endorsement services from influencers. To make it easier for consumers to get D'Wan Shoes products, they must have an online store in the marketplace or company social media accounts.